Rebuilding the Implementation of Sanctions for Ethical Code Violations by Civil Servants by Investigators Based on Values of Justice - Rabiatul Adawiyah; Suprapto Suprapto; Saprudin Saprudin; Kamran Azizli (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The enforcement of ethical codes within the civil service is a fundamental pillar for maintaining public trust and bureaucratic integrity. However, the implementation of disciplinary sanctions for Civil Servants (Aparatur Sipil Negara or ASN) in Indonesia currently faces significant challenges regarding fairness and consistency. (Problem) The core issue lies in the broad administrative discretion possessed by investigators (Tim Pemeriksa) under Government Regulation No. 94 of 2021, which often leads to subjective, legalistic, and disproportionate sanctioning without considering substantive justice. This study aims to analyze the weaknesses of the current sanction implementation mechanism and proposes a reconstruction of the investigators' authority based on the value of justice (Nilai Keadilan). Using a normative juridical approach and conceptual analysis, this research examines current regulations and compares them with the principles of Dignified Justice. The study finds that the current positivistic approach tends to ignore the human aspect and restorative potential of the sanctions. Consequently, a reconstructed model is proposed where investigators must integrate ethical deliberation and justice values into their examination process, ensuring sanctions are not merely punitive but also corrective and fair.